2013
DOI: 10.1002/pbc.24579
|View full text |Cite
|
Sign up to set email alerts
|

Mismatch DNA repair mRNA expression profiles in oral melanin pigmentation lesion and hamartomatous polyp of a child with peutz–jeghers syndrome

Abstract: Mismatch DNA repair (MMR) mRNA expression analysis was performed on a biopsy of oral mucosa melanin pigmentation lesion, a hamartomatous polyp and peripheral blood derived from a 12-year-old child with Peutz-Jeghers Syndrome (PJS). We present a deficient MMR system, in a PJS patient, which demonstrated low mRNA levels of hMSH6 and hPMS2 and an increasing MMR deficiency from the non-dysplastic lesion to hamartomatous polyp of PJS with a high risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It is clear that balanced expression levels of components of the MMR system are essential for effective repair functions (2,32,45). Vageli et al previously demonstrated an association between an imbalanced mRNA phenotype of MMR genes and cancer progression in human lung, colorectal and urinary bladder cancer (18,(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…It is clear that balanced expression levels of components of the MMR system are essential for effective repair functions (2,32,45). Vageli et al previously demonstrated an association between an imbalanced mRNA phenotype of MMR genes and cancer progression in human lung, colorectal and urinary bladder cancer (18,(46)(47)(48)(49).…”
mentioning
confidence: 99%
“…Studies have shown that repairing specific types of DNA damage requires SLX4 and other endonucleases to participate together[ 22 ]. At present, it is believed that[ 27 - 29 ] the loss of DNA MMR genes causes the accumulation of mismatches in the process of DNA replication, resulting in the occurrence of microsatellite instability and partial junctions. Colorectal cancer has obvious genetic characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Pigmentation features may mimic xeroderma pigmentosum in the early stages (xeroderma pigmentosum is an extreme sun sensitivity-associated high risk of skin cancer) (19). Melanin hyperpigmentation present on a patient who is not previously known to have the syndrome must be biopsied in order to obtain a clear diagnostic (20). Previous findings have revealed a certain genotype-phenotype correlation of the STK11/LKB1 gene involving the fact that more severe dermatological findings are correlated with a more aggressive profile of gastro-intestinal hamartomatous polyps (21).…”
Section: Skin and Mucosal Manifestationsmentioning
confidence: 99%